A bivalent mRNA vaccine against RSV infection in rodent models - Liu, Juan; Zhao, Hanqing; Wang, Wenhao; Yang, Binbin; Zhang, Naifang; Zhang, Yu; Qian, Jie; Ma, Qiaofang; Lu, Yankun; Han, Huafeng; Yang, Yongsheng (Frontiers in Immunology, 2025)
Because of the higher conservation of RSV Fusion (F) protein than the glycoprotein (G) across RSV strains and serotypes, the majority of vaccine candidates targets to viral fusion protein (F) rather than glycoprotein to elicit a broader range of protective neutralizing antibodies from infection. In this study, we screened two chemically modified mRNA vaccines expressing RSV prefusion stabilized protein (preF) targeting RSV A2 and B subtypes. After immunization, the antigen-specific binding antibody, neutralizing antibody, and T cell-mediated immune response were evaluated. After challenge with live RSV A2 virus in cotton rats, the protection and safety of vaccine was further evaluated. The results showed that the mRNA vaccine candidates elicited robust antigen-specific binding antibody, neutralizing antibody responses and Th1-biased T-cell responses in both mice and cotton rats. Moreover, cotton rats vaccinated with mRNA vaccine, lung pathology and lung infectious viral loads were significantly reduced, and no vaccine enhanced respiratory disease (VERD) happened. These results collectively demonstrated that mRNA-based vaccine induced strong humoral and cellular immunity, provided outstanding protection against both RSV A2 and RSV B subtypes in rodent animals as well. Our data demonstrated that these mRNA vaccines should be further evaluated in clinical trials.